Designing APV in Jungle (Audio, Picture And Video) to Learn English Speaking Skills - Agustina, Ulfa Wulan; Muslimah, Khairunnisa Nur; Fikri, Ahmad Kanzul (Jurnal Bahasa dan Sastra, 2021)
The purpose of this research is to improve students’ English skills in vocabulary mastery through the application media containing audio and video images. This study uses R&D design. This research was conducted on grade VIII students of MTS Ma’arif 4 Mantup, Lamongan, with a total of 25 students. Data collection in this study was obtained by sharing quisioner, to know the needs and obstacles experienced by students in learning vocabulary in English. To meet validity and reliability, the researchers used two validators tasked with testing the feasibility of learning media for students to use. Testers consist of material experts and media design experts. The results of this study show that application-based learning media is feasible to use. Improvements can be seen from the use of data analysis techniques to calculate scores from questionnaires using Linkert scale techniques with 5 answer options. According to the assessment by 25 students, the total score obtained is 1066, the total score is then calculated using the formula described earlier to determine the feasibility of learning media. The average score obtained from the respondence is 42, the data then again calculates. So, the results of assessment by respondents are 4.2 which fall into the category of good and worth to use. The benefits of research conducted to make it easier for students to learn English vocabulary using application-based media. Based on the results of the study, students can conclude that it is easier to learn English vocabulary using a media.